Portal vein tumour thrombosis radiotherapy improves the treatment outcomes of immunotherapy plus bevacizumab in hepatocellular carcinoma: a multicentre real-world analysis with propensity score matching - Tang, Cuiping; He, Qin; Feng, Jian; Liao, Ziyue; Peng, Yunli; Gao, Jian (Frontiers in Immunology, 2023)
Background: This study aimed to evaluate the efficacy and safety of sequential immune checkpoint inhibitors (ICIs) plus bevacizumab therapy after radiotherapy for portal vein tumour thrombosis (PVTT) in patients with hepatocellular carcinoma (HCC).Methods: Retrospective data were collected from 113 patients with HCC with PVTT.Patients in the PVTT radiotherapy (radiotherapy + ICIs + bevacizumab) and control groups (ICIs + bevacizumab) were enrolled according to propensity score matching (PSM) analysis (1:1). The differences in progression-free survival (PFS), objective response rate (ORR), disease control rate (DCR), and potential factors affecting PFS between the groups were analysed. The adverse events (AEs) were compared between the two groups.Results: There were 47 patients in the two groups after PSM (1:1). The differences in neutrophil and lymphocyte counts, neutrophil-to-lymphocyte ratio (NLR), CRP, and CD4, CD8, and CD4-to-CD8 ratio before and after radiotherapy for PVTT (P < 0.05) in the PVTT radiotherapy group were significant. The patients in the PVTT radiotherapy group had a longer PFS (median, 9.6 vs. 5.4 months, P < 0.001), and the PFS rates of 3, 6, 9, and 12 months were 97.87% vs. 94.19%, 80.85% vs. 44.68%, 53.19% vs. 6.38%, and 23.40% vs. 0.00%, respectively (P < 0.001). There were also significant differences in the ORR (48.94% vs. 27.66%, P = 0.0339) and DCR (97.87% vs. 82.98%, P = 0.0141) between the two groups, and no serious AEs were observed. Multivariate Cox analysis showed that AFP expression, gross classification of HCC, PVTT type, extrahepatic metastasis, PVTT radiotherapy, and reduction in PVTT were independent factors influencing PFS (P < 0.05).Conclusions: Sequential ICIs plus bevacizumab therapy after radiotherapy for PVTT in patients with HCC is safe and feasible and may further prolong the PFS of patients.